New species of Pseudosmittia Edwards, 1932 and new records of Allocladius Kieffer, 1913 (Diptera: Chironomidae, Orthocladiinae) from South America - Mauad, Melina (2013)
Three new species of Pseudosmittia Edwards from the Neotropical region, P. sætheri, P. larga and P. trapezoidea, are described and figured as males. Allocladius fortispinatus (Edwards), A. globosus Andersen et al. and A. quadrus Andersen et al. are redescribed on the basis of new material and their geographical distribution updated. A phylogenetic analysis was performed in order to assess the phylogenetic relationships of the new species. As a result, the species P. sætheri and P. larga are found to be sister species belonging to the angusta group. The species P. trapezoidea is the sister group of the clade ((P. propetropis (P. tropis – P. lamellata)) and belongs to the brevifurcata group sensu lato.